Discovery of living Potamolepidae (Porifera: Spongillina) from Nearctic freshwater with description of a new genus - Copeland, John; Pronzato, Roberto; Manconi, Renata (Zootaxa, 2015)
We report here the first record of a living Potamolepidae (Cherokeesia n. gen.) from the Nearctic Region and from the northern hemisphere. The new species Cherokeesia armata from southern Appalachians diverges at generic and specific level from all the other known taxa of the family Potamolepidae in its unique combination of diagnostic traits: gemmular theca armed by gemmuloscleres ranging from small strongyle-like spicules to stout, large oxeas; absence of pneumatic layer; spiny oxeas as main skeleton megascleres; irregular, slender pauci- to uni-spicular skeletal network. The most similar species belong to the genera Potamophloios and Oncosclera. The circumtropical biogeographic pattern of extant Potamolepidae, previously considered of Gondwanian to Gondwanian-like origin, is enlarged to the Nearctic. The present Tennessee discovery confirms a wider range of the family. An updated species inventory of Nearctic Spongillina, a checklist of the family Potamolepidae at the global level together with a key to the genera of Potamolepidae are also provided.